Recent advances in nZVI@MOF composites for Cr(VI) removal: A comprehensive review - Safina Zafar; Shumaila Bibi; Mohamed H. Helal; Haider Ali; Guilherme Luiz Dotto; Zeinhom M. El-Bahy; Muhammad Ahmad Wattoo; Aziz ur Rehman (Journal of Environmental Chemical Engineering, 2026)

Short-Term Soil Health Responses to Biochar and Irrigation in a Sandy Loam Soil - Md Ali Haider; Jim J. Wang; Syam K. Dodla; Krizzia Guardado; Aziz Ahmed; Changyoon Jeong; Lewis A. Gaston (Journal of Soil Science and Plant Nutrition, 2026)
This study was conducted to determine how irrigation alters the effects of biochar on soil health parameters in a coarse texture soil for two consecutive growing seasons. Surface soil (0–15 cm) samples from a split-plot randomized block design (main plots, unirrigated and irrigated; subplots, 0 and 11.2 Mg ha − 1 biochar) taken after soybean ( Glycine max ) harvest in 2022 and 2023 were analyzed for electrical conductivity, pH, labile and total C, inorganic and total N, respiration rate, activities of four extracellular enzymes, and phospholipid fatty acid profiles. Yield was also measured. Neither biochar nor irrigation increased yield. Biochar increased pH and β-glucosidase activity but decreased phosphatase activity. Irrigation reduced organic C, respiration and activities of all enzymes except arylsulfatase. Principle component analysis showed that parameters related to organic C turnover were important without irrigation. Structural equation modeling for respiration rate found small positive effects of phosphatase activity and labile C with irrigation ( P < 0.10), but large positive effect of phosphatase without ( P < 0.01). An interrelationship of other enzymes and microbial biomass was important to respiration without irrigation, though not with irrigation. The effect of irrigation on soil health parameters in a coarse texture soil for two growing seasons was greater than the effect of biochar.

Synergistic photo-assisted AOPs using acid-modified biochar: Enhanced micropollutant levofloxacin degradation in industrial wastewater - Muhammad Irtaza Sajjad Haider; Guijian Liu; Balal Yousaf; Muhammad Arif; Kiran Aziz; Bisma Sattar; Muhammad Zeeshan Gulzar; Hameer Chand; Ruijia Liu (Desalination, 2026)

Green photocatalytic degradation of methylene green dye using oxalic acid and its metal complexes: Mechanistic and predictive insights from ANN, RSM, and DFT studies - Mohammad Tauseef Haider; Rizwan Ashraf; Talib H. Mawat; Faisal Jamil; Adnan Majeed; Anam Shahzadi; Faisal Qaleel; Haris Nadeem; Sabha Khalid; Asma Rehman; Sadia Aziz; Maryam Khalid; et al. (Journal of Water Process Engineering, 2026)

Plant-derived biostimulants: Emerging trends, breakthroughs and challenges in 2024 - Qurat Ul Ain Hyder; Abida Aziz; Muhammad Farooq Azhar; Muhammad Hasnain Haider; Nazim Hussain (Organic Agriculture, 2026)

Optimal Co doping to Ni-based catalyst to promote partial oxidation of methane for syngas production - Muzafar Abbas; Liaquat Aziz; Syed Mushtaq; Arsalan Haider; Min Gie Jung; Dong Wook Kwon; Gun-hee Moon; Sang Hoon Kim (Chemical Engineering Journal, 2026)

Transformation of wet chemically derived ZnGa-LDH to ZnO:GaN nano-alloys for PMS activated wastewater remediation - Yasir Abbas; Kanwal Shabbir; Haider Aziz; Ijaz Hussain; Hafiz M. Adeel Sharif; Muhammad Ahsan Iqbal; Majid Basharat; Haoliang Wang; Niaz Ali Khan (Journal of Environmental Chemical Engineering, 2025)

Sustainable biochar ferrite nanocomposites for high performance electrochemical energy storage systems - Diksha Palariya; Arun Bughani; Mohammad Aziz; Jyoti Maheshwari; Mohammad Ghulam Haider Zaidi; Sameena Mehtab (Waste Disposal & Sustainable Energy, 2025)

Microplastic contamination in agricultural soils from mulch films and organic amendments: Transformation mechanism, soil-Biota toxicity, and future perspectives - Bisma Sattar; Guijian Liu; Balal Yousaf; Muhammad Arif; Muhammad Zeeshan Gulzar; Muhammad Irtaza Sajjad Haider; Rabia Safeer; Samra Ijaz; Muhammad Awais Haider; Kiran Aziz (Waste Management, 2025)

Effect of Phosphorus Modified Cotton Stick Biochar on Growth, Photosynthesis, Enzymatic Activities and Lead (Pb) Uptake in Tomato Plants Grown in Pb-contaminated Soil - Zaffar Malik; Aleena Shabir; Ahmad Ali; Muhammad Naveed Aslam; Humera Aziz; Syed Farhan Haider Bukhari; Sana Noreen; Usama Ali Tahir; Muhammad Rizwan (Journal of Soil Science and Plant Nutrition, 2025)

Innovative transformation of palm oil biomass waste into sustainable biofuel: Technological breakthroughs and future prospects - Tonni Agustiono Kurniawan; Mehwish Ali; Ayesha Mohyuddin; Ahtisham Haider; Mohd Hafiz Dzarfan Othman; Abdelkader Anouzla; Hui Hwang Goh; Dongdong Zhang; Wei Dai; Faissal Aziz; Muhammad Imran Khan; Imran Ali; et al. (Process Safety and Environmental Protection, 2025)

Catalytic synthesis of selenium nanoparticles by gram-negative Aeromonas sobria and their application for removal of toxic dyes - Soma Sardar Barawi; Karzan Ahmed Qurbani; Seenaa Muhammed Ali; Safin Hassan Hussein; Dara Muhammed Aziz; Rawezh Omer Hamasalih; Razhan Bakhtyar Ahmed; Haider Mousa Hamzah (Biologia, 2024)

Synergistic interactions and reaction mechanisms of biochar surface functionalities in antibiotics removal from industrial wastewater - Muhammad Irtaza Sajjad Haider; Guijian Liu; Balal Yousaf; Muhammad Arif; Kiran Aziz; Aniqa Ashraf; Rabia Safeer; Samra Ijaz; Krzysztof Pikon (Environmental Pollution, 2024)

Smartphone-assimilated colorimetric sensor for sub-nanomolar emamectin detection via KA30 capped silver nanoparticles in food, bio-fluids and water samples - Aziz Balouch; Kashif Hussain; Ayman Nafady; Abdul Jabbar; Sufian Rasheed; Sumaira Kanwal; Sadia Haider; Razium Ali Soomro; Sirajuddin; Muhammad Raza Shah (Food Chemistry, 2024)

Cultivating sustainability: Harnessing biochar-derived composites for carbon-neutral wastewater treatment - Tonni Agustiono Kurniawan; Shahnoor Ali; Ayesha Mohyuddin; Ahtisham Haider; Mamoona Riaz; Sajid Khan; Mohd Hafiz Dzarfan Othman; Hui Hwang Goh; Abdelkader Anouzla; Faissal Aziz; Imran Ali (Process Safety and Environmental Protection, 2024)

Exploring Rare Earth Element Doped Nanocomposites as Promising Photocatalysts for Dyes Degradation in Water - Diksha Palariya; Sameena Mehtab; Mohammad Aziz; Mohammad Ghulam Haider Zaidi (Water, Air, & Soil Pollution, 2024)

Effect of different concentrations of resveratrol on nuclear maturation and in-vitro development competence of oocytes of Nili Ravi buffalo - Samar Wafa Kabeer; Amjad Riaz; Aziz Ul-Rahman; Rana Muhammad Shahbakht; Ahsan Anjum; Hafeez ur Rehman Ali Khera; Ali Haider; Faisal Riaz; Riffat Yasin; Muhammad Yaseen; Muhammad Saleem; Naheed Bano; et al. (Tropical Animal Health and Production, 2024)

Tackling microplastics pollution in global environment through integration of applied technology, policy instruments, and legislation - Tonni Agustiono Kurniawan; Ahtisham Haider; Ayesha Mohyuddin; Rida Fatima; Muhammad Salman; Anila Shaheen; Hafiz Muhammad Ahmad; Hussein E. Al-Hazmi; Mohd Hafiz Dzarfan Othman; Faissal Aziz; Abdelkader Anouzla; Imran Ali (Journal of Environmental Management, 2023)

Exploring environment sensitivity to fiscal and monetary policies in China: using ecological footprints as a contemporary proxy - Usman Saleem Yousaf; Farhan Ali; Shabib Haider Syed; Babar Aziz; Saima Sarwar (Environmental Science and Pollution Research, 2022)

Performance and microbial community analysis in a modified anaerobic inclining-baffled reactor treating recycled paper mill effluent - Haider M. Zwain; Hamidi Abdul Aziz; Wun Jern Ng; Irvan Dahlan (Environmental Science and Pollution Research, 2017)